Alteration of Aging‐Dependent MicroRNAs in Idiopathic Pulmonary Fibrosis. Issue 7 (25th August 2015) - Nho, Richard Seonghun; Gurwitz, David
ABSTRACT <table-wrap position="anchor" orientation="portrait"> Preclinical Research </table-wrap> Idiopathic Pulmonary Fibrosis (IPF) is the most severe fibrotic lung disease and characterized by the accumulation of (myo)fibroblasts and collagen within the alveolar wall resulting in obliteration of the gas‐exchange surface. Although the detailed pathogenesis is not understood, recent studies have found that several microRNAs (miRNAs) are associated with the progression of lung diseases including IPF. IPF is a fibrotic disease and, most frequently found in an aged population. In this review, the functional roles of miRNAs that are deregulated in IPF progression are discussed together with how aging affects the miRNA signature, altering the fibroblast phenotype and promoting lung fibrosis. Finally, the possibility of targeting miRNAs as a therapeutic approach for the treatment of IPF is discussed. Drug Dev Res 76 : 343–353, 2015. © 2015 Wiley Periodicals, Inc.